2018 AIAA Aerospace Sciences Meeting 2018
DOI: 10.2514/6.2018-0167
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Study on AC-DBD Plasma and Electrical Heating for Aircraft Icing Mitigation

Abstract: A comparison study of utilizing thermal effects of a Dielectric-Barrier-Discharge (DBD) plasma actuator and a conventional electrical film heater for aircraft icing mitigation was performed in an Icing Research Tunnel available at Iowa State University (i.e., ISU -IRT). A NACA0012 airfoil/wing model embedded with an AC-DBD plasma actuator and a conventional electrical film heater over the airfoil surface was tested under a typical aircraft icing condition. While a high-speed imaging system was used to record t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…In the context of this study, another report by Liu et al [176] compared the actuation of DBD plasma actuators with conventional electrical heating using the same experimental setup and conditions as reported in [149]. The reported results are consistent with the previous information.…”
Section: Plasma Actuators For Deicing and Ice Formation Preventionsupporting
confidence: 88%
“…In the context of this study, another report by Liu et al [176] compared the actuation of DBD plasma actuators with conventional electrical heating using the same experimental setup and conditions as reported in [149]. The reported results are consistent with the previous information.…”
Section: Plasma Actuators For Deicing and Ice Formation Preventionsupporting
confidence: 88%
“…The effect and efficiency of nSDBD-based de-icing on aircraft wings were confirmed in an early experiment [19] in 2016. Later, the concept of plasma-assisted anti-icing or icing control was proposed [20,21] and a rich set of experiments were conducted [22][23][24][25][26][27][28][29][30][31][32][33][34] in the following years. It was found that at the same total power input, an acSDBD has a better anti-/de-icing performance in comparison to a conventional electrical film heater if a duty-cycle modulation [23,28] is used.…”
Section: Introductionmentioning
confidence: 99%
“…Later, the concept of plasma-assisted anti-icing or icing control was proposed [20,21] and a rich set of experiments were conducted [22][23][24][25][26][27][28][29][30][31][32][33][34] in the following years. It was found that at the same total power input, an acSDBD has a better anti-/de-icing performance in comparison to a conventional electrical film heater if a duty-cycle modulation [23,28] is used. The temperature distributions of acSDBDs and nSDBDs were studied using an infrared (IR)thermal imaging system [26,27]; the authors claimed that heat dissipation for nSDBDs is more effective than for acSDBDs, suggesting better anti-icing performance.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that plasma actuators are effective anti-icing/deicing devices, and nanosecond dielectric barrier discharge (NSDBD) plasma actuators have been found to perform better than alternating current DBD plasma actuators [152][153][154][155]. Zhu et al [156,157] investigated the heating performance of NSDBD and demonstrated that it can heat up quickly and has an ice-proof heating effect.…”
Section: Plasma Anti-icing/deicingmentioning
confidence: 99%